Um estudo sobre as armadilhas magneto-ópticas com feixes auxiliares - Araújo, Ascânio Dias (1996)
Recently, Flemming et al [Opt. Lett. 24, 2529 (1995)] have reported an approximately 2-fold improvement in the number of trapped atoms by using a two-color magneto-optical trap. In this work, we present a theoretical discussion on the enhancement of the capture process of sodium atoms in the conventional magneto-optical trap besides two color configuration. Here we show by using a simple theoretical model to describe the capture process in the ideal-gas mode, that we are able of describing the main features of these magneto-optical trap configurations.